Global Inequality and Poverty Crisis: ASEAN Ineffective Role in the Mekong River Conflict Resolution - NOR ATIQAH MOHD ISA (Universitas Airlangga, 2022)
Mekong River, known as the beating heart of mainland Southeast Asia, has been facing degradation of its natural flow of water due to anthropogenic activities across the river initiated by the Chinese government through the construction of hydropower dams. As a consequence, the river which provides a key source of water supplies and resources for the millions of people who live across its watershed has suffered significantly resulting in inequality and poverty in the community. The purpose of this study is to examine the root causes of inequality and poverty in the Lower Mekong region, as well as to identify ASEAN’s role in responding to the situation. The findings revealed that due to the Belt and Road Initiative (BRI) projects through the construction of dams along the river as well as ASEAN’s inability to resolve and address the crisis owing to economic dependence and difficulty to reach a consensus among its members has been a contributing factor to the ineffectiveness of ASEAN in the conflict resolution. From the findings, it can be concluded that China’s financial hegemony over the Mekong countries can have an impact on the region’s future levels of poverty and inequality.